Real world treatment patterns for recurrent and metastatic head and neck cancer in the post-KEYNOTE 048 era - Lee, Daniel Y.; Pan, Alexander; Yaskolko, Maxim; Chiorazzi, Michael; Bhatia, Aarti; Burtness, Barbara; Ishizuka, Jeffrey J. (Frontiers in Oncology, 2025)
BackgroundWhile KEYNOTE-048 established anti-PD1 with or without chemotherapy as first-line treatment for recurrent and metastatic head and neck squamous cell carcinoma (HNSCC) with combined positive score (CPS) ≥ 1, treatment choice remains ambiguous given additional toxicity of combination treatment.MethodsPatients treated first-line with anti-PD1 monotherapy, anti-PD1+chemotherapy, or cetuximab+chemotherapy in the Flatiron Health database were included. Treatment group differences were assessed with chi-squared and t-tests, and selection factors were analyzed with logistic regressions. Survival was assessed with Kaplan-Meier curves, log-rank tests, and Cox regressions.ResultsOf 2577 patients included, Anti-PD1 monotherapy (n=1410) improved survival over cetuximab+chemotherapy (n=577, median survival 14.6 vs. 12.6 months, p=0.015), while anti-PD1+chemotherapy (n=590) showed a nonsignificant trend towards improvement (median survival 14.3 vs. 12.6 months, p=0.053). In HPV-associated disease, survival was equal between regimens. Addition of chemotherapy improved survival over anti-PD1 monotherapy in non-HPV associated tumors with CPS 1-9 (median survival 18.0 vs. 10.3 months, p=0.029) and in oral cavity primaries (median survival 10.3 vs. 7.6 months, p=0.003).ConclusionsSubgroups of patients with recurrent or metastatic HNSCC, including non-HPV associated disease with CPS 1-9 and oral cavity primaries, may derive benefits from the addition of chemotherapy to anti-PD1 therapy.